2008
DOI: 10.1111/j.1601-0825.2007.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Palatal zygomycosis: experience of 21 cases

Abstract: Zygomycosis with palatal involvement occurs in around 18% of cases, usually associated with RC modalities; it has an acute and generally lethal course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 25 publications
1
50
0
9
Order By: Relevance
“…One of our patients had a very distinct clinical presentation of a small localized ulcer on the hard palate; this was an immunosuppressed patient with type-2 acute lymphoblastic leukemia. This clinical manifestation was very different from candidiasis, which is more superficial, and bore a close resemblance to ulcers caused by zygomycosis and aspergillosis, resulting in a very aggressive palatinecerebral condition with a poor prognosis (20). This has been reported for some patients (19) with esophageal ulcerations (21); oral ulcers in dogs have also been reported (22).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…One of our patients had a very distinct clinical presentation of a small localized ulcer on the hard palate; this was an immunosuppressed patient with type-2 acute lymphoblastic leukemia. This clinical manifestation was very different from candidiasis, which is more superficial, and bore a close resemblance to ulcers caused by zygomycosis and aspergillosis, resulting in a very aggressive palatinecerebral condition with a poor prognosis (20). This has been reported for some patients (19) with esophageal ulcerations (21); oral ulcers in dogs have also been reported (22).…”
Section: Discussionmentioning
confidence: 82%
“…Therefore it is important to be aware that the normal flora of the skin and mouth can lead to contamination of catheters, this condition has been previously (4,17,20,22).…”
Section: Discussionmentioning
confidence: 99%
“…The most common form is the rhinocerebral one [3,[8][9][10] and it is found in 44-49% of all detected zygomycosis. Retrospective analysis of 98 cases made by Vaezi et al [11] showed that rhinocerebral form, characterized by the highest mortality rate was detected most frequently in the gathered data (about 48.9% of all clinical subtypes of rhinocerebral zygomycosis).…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…For comparison: the sinonasal -7.1% and sinonasaloorbital -6.1% forms were not often found. This disease may occur in all patients regardless of age and gender [9,12]. Often the most vulnerable age group were young adults with varying degrees of deficiency of the immune system and also those treated for other systemic diseases.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…The oral involvement of this condition may also occur and has been reported in the literature. As in cutaneous mucormycosis, injured tissue in the oral cavity can be a suitable port of entry (6).…”
Section: Introductionmentioning
confidence: 99%